SYSTEMATIZATION OF NURSING CARE IN A NEONATAL UNIT - Rosa Aparecida Nogueira Moreira; Larissa Daniele Bispo Pereira; Ana Érica Oliveira Brito Siqueira; Lívia Moreira Barros; Natasha Marques Frota; Izaildo Tavares Luna (Universidade Federal do Paraná, 2012)
Through this research, with a qualitative approach, it was aimed to identify the difficulties and contributions of the Systematization of Nursing Care in a neonatal unit in the view of the nurses. Information was collected in 2011 through semi-structured interviews with 7 nurses in Fortaleza-Ceará and was organized through the technique of content analysis. The categories which emerged evidenced that the Systematization of Nursing Care is riddled with difficulties, is fragmented and with incomplete records. The lack of time, the insufficient number of nurses and the lack of an instrument specifically for recording information emerged as principal obstacles to implantation. It was possible to perceive, by means of the reports, that the Systematization of Nursing Care makes possible the autonomy necessary for carrying out work which is conscious, efficient and rewarding from the point of view of positive results in care given to the newborn.